Notes on Scottish Coins: (1) Rex Scottorum Pennies of David II.; (2) Edinburgh Light Groats of Robert III.; (3) Some James II. Groats of the Third Variety of the Fleur-de-lis Groats; and (4) Gilbert Kirkwood's Mark on a Gold Coin of James V (Proceedings of the Society of Antiquaries of Scotland, 1938)
All the coin types are described in detail and an attempt is made to classify them typologically. Some previously unpublished coins are included.